Heuristic modeling of the process of milling aviation parts with opposed end mills by synthesis of a predictive model - E. A. Shestakova; V. O. Ievlev; R. M. Yanbaev (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
The paper presents a comparative analysis of existing milling technologies. The influence of the main negative factors affecting the quality of machined surfaces is revealed. Optimal schemes for machining with opposed cutters are proposed. The modeling of milling processes with oppositely located cutters of thin-walled extended aircraft parts is carried out. The process under study is described by the appropriate physical quantities. A system of eight characteristic equations describing the modes and components of cutting forces, as well as the dynamics of the milling process, is considered. A characteristic equation in dimensionless form is obtained, linking the geometric parameters of the cutting tool, the feed rate and the rotation frequency of the cutter. After checking the synthesized mathematical model by calculation, an experimental check of the proposed model for adequacy to the real process was carried out when machining the appropriate walls of blanks of ribs and beams made of aluminum alloy, manufactured by stamping, with oppositely located end mills. The edges of wells and pockets of aircraft parts were machined in small-scale production conditions. Roughness measurements were taken using a profilograph-profilometer. Optimum values of exponents and appropriate coefficients for simplexes of the mathematical model were determined. A comparative analysis of practical indicators and simulated data of the milling process was carried out. The resulting model allows predicting the results of machining by the proposed method with an error of 10…15%.